Evaluación de la adaptación de siete cultivares de brócoli (Brassica Oleracea Var. Itálica) en el barrio Anchilivi, Salcedo, Cotopaxi, 2022. - Oña Toapanta, Jessica Paola (2023)
This research was conducted in the Anchilivi neighborhood, Canton Salcedo, Cotopaxi Province. The objective was to evaluate the adaptation of seven broccoli cultivars (Brassica oleracea var. Italica). The cultivars were provided by the company "Semillas Capelo." The study cultivars are MKS-B116, MKS-B106, EMBR 266, EMBR 940, HAIYAN, BR1801, and Avenger, which is the control. Three replications were established, resulting in 21 experimental units, each experimental unit measuring 10m2, with a total area of 434 m2, a completely randomized experimental design DBCA was used. The Tukey test was performed at 5% of the statistical significance variables. Quantitative variables (equatorial diameter, height, weight, rejection, % yield, days to harvest) and qualitative variables (shape, color, compactness, grain size, uniformity, and tolerance to pests and diseases) were recorded. The main results indicate that the cultivars adapted favorably to the study area. The variety with the best result was MKS-B106 in the variable height at 60 days (46,23), the best variety was EMBR 940 in the variables pellet diameter (15.47 cm), pellet weight (357.6g), rejection (109, 43 g), with the best yield (13402 kg/ha) and requires 86 days to be harvest, surpassing the avenger variety which is the commercial one in plant height (43.63 cm), pellet diameter (15.17 cm), pellet weight (343.87 g), rejection (135.33 g), with a yield (5419 kg/ha). The second best variety is HAIYAN with the results in the diameter of the pellet (16.00 cm), the weight of the pellet (338.7 g), rejection (111.67 g), yield (11168 kg/ha) and has 82 days to be harvested, and the variety is precocious. EMBR 940 proved to be the most adaptable, and it is recommended to cultivate the variety in the Anchilivi zone of Salcedo canton to obtain a quality product.